The role of microbiota in the development of allergic diseases - Oksana Boyarchuk; Andrii Chornomydz; Iryna Chornomydz; Halyna Krytska; Ihor Horishniy (Health Problems of Civilization, 2019)
Scientific progress, industrial development, urbanization, and the "sterile" way of life have a significant negative side, namely, the sustained growth of allergic diseases. The "hygienic theory" is used to explain the unceasing increase in the incidence of allergies in the population. At the same time, an important link in the development of allergic diseases is the microbiological environment and our own microbiota. In our literature review we gathered new data on the pathogenetic relationships between the violation of the quantitative and qualitative composition of our microbiocenosis and the development of allergic diseases. The basic mechanisms by which microbiota influence the development of an allergic process have been established, in particular: influence on T-cell immunity, synthesis of cytokines, etc. In this review, particular attention is paid to factors that lead to microbiocenosis and contribute to the development of allergies. Among them it is worth to highlight inappropriate nutrition, "sterile" style of life, widespread using of antiseptics and antibiotics, etc. Therefore, the most important step in the prevention of allergic diseases is the modification of lifestyle, breastfeeding of children, frequent staying in the open air and contact with nature, rational use of antiseptics and antibiotics.